Influence of concurrent capecitabine based chemoradiotherapy with bevacizumab on the survival rate, late toxicity and health-related quality of life in locally advanced rectal cancer - Velenik, Vaneja (Radiology and oncology (Ljubljana), 2020)
Few studies reported early results on efficacy, toxicity of combined modality treatment for locally advanced rectal cancer (LARC) by adding bevacizumab to preoperative chemoradiotherapy, but long-term data on survival, and late complications are lacking. Further, none of the studies reported on the assessment of quality of life (QOL). Patients and methods. After more than 5 years of follow-up, we updated the results of our previous phase II trial in 61 patients with LARC treated with neoadjuvant capecitabine, radiotherapy and bevacizumab (CRAB study) before surgery and adjuvant chemotherapy. Secondary endpoints of updated analysis were local control (LC), disease free (DFS) and overall survival (OS), late toxicity and longitudinal health related QOL (before starting the treatment and one year after the treatment) with questionnaire EORTC QLQ-C30 and EORTC QLQ-CR38. Results. Median follow-up was 67 months. During the follow-up period, 16 patients (26.7%) died. The 5-year OS, DFS and LC rate were 72.2%, 70% and 92.4%. Patients with pathological positive nodes or pathological T3%4 tumors had significantly worse survival than patients with pathological negative nodes or T0%2 tumors. Nine patients (14.8%) developed grade % 3 late complications of combined modality treatment, first event 12 months and last 87 months after operation (median time 48 months). Based on EORTC QLQ-C30 scores one year after treatment there were no significant changes in global QOL and three symptoms (pain, insomnia and diarrhea), but physical and social functioning significantly decreased. Based on QLQ-CR38 scores body image scores significantly increase, problems with weight loss significantly decrease, but sexual dysfunction in men and chemotherapy side effects significantly increase. Conclusions. Patients with LARC and high risk factors, such as positive pathological lymph nodes and high pathological T stage, deserve more aggressive treatment in the light of improving long-term survival results. Patients after multimodality treatment should be given greater attention to the regulation of individual aspects of quality of life and the occurrence of late side effects.
Keywords: bevacizumab; danka; kemoradioterapija; radiološko zdravljenje; rak (medicina); zdravljenje